The Role and Function of the Mosque in the Development of Islamic Culture: A Case Study at Sunan Kudus Mosque Ngadiluwih, Kediri - Iqlima Zahari; Widyatmoko Widyatmoko (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The mosque is an emblem of Islamic cultural heritage and a place of worship for Muslims. It serves as a place for i'tikaf and prayer. This research sought to determine the extent of the role, function, and contribution of the Sunan Kudus mosque in preserving and developing Islamic culture in Ngadiluwih. It employs qualitative research methods and a historical and social approach. Data was collected through interviews, observations, and literature study. Data analysis involved gathering all of the data before reducing and classifying it and subsequently drawing conclusions. First, the study finds that the presence of the Sunan Kudus mosque has profoundly shaped the existence, culture, and symbols of Islam in Ngadiluwih. Second, the Sunan Kudus mosque, with all its activities, makes a major contribution to the surrounding community. Third, beyond its function on a small scale as a site of prayer, the mosque plays a role on a larger scale, namely as a hub for learning, teaching, discussions, recitation, social activities, and so on, tailored to the characteristics of the majority community.